Asparagus - Marr, Charles W.; Tisserat, Ned (My University, 1997)
This publication is for commercial vegetable production specifically asparagus in Kansas.
MF1093_1997_12
Keywords: MF1093; Crops; Fruits and Vegetables; Equipment and Structures; MF